The Cambridge social history of modern Ireland - Biagini, Eugenio F.; Daly, Mary E. (Cambridge : Cambridge University Press, 2017)
Covering three centuries of unprecedented demographic and economic changes, this textbook is an authoritative and comprehensive view of the shaping of Irish society, at home and abroad, from the famine of 1740 to the present day. The first major work on the history of modern Ireland to adopt a social history perspective, it focuses on the experiences and agency of Irish men, women and children, Catholics and Protestants, and in the North, South and the diaspora. An international team of leading scholars survey key changes in population, the economy, occupations, property ownership, class and migration, and also consider the interaction of the individual and the state through welfare, education, crime and policing. Drawing on a wide range of disciplinary approaches and consistently setting Irish developments in a wider European and global context, this is an invaluable resource for courses on modern Irish history and Irish studies.
Part I. Geography, occupations and social classes -- Irish demography since 1740 / J. Fitzgerald -- Occupation, poverty and social class in pre-famine Ireland, 1740-1850 / P. Solar -- Famine and famine relief, 1740-2000 / M.E. Daly -- Languages and identities / G.O Tuathaigh -- Catholic Ireland, 1740-2016 / C. Barr and D.O Corrain -- Protestant Ireland, 1740-2016 / A. Holmes and E. Biagini -- Town and city / D. Dickson -- The farmers since 1850 / P. Rouse -- The Irish working class and the role of the state, 1850-2016 / H. Patterson -- The big house / T. Dooley -- Elite formation, the professions, industry and the middle-class / J. Ruane and J. Todd -- Part II. People, culture and communities -- Consumption, living standards and the state / A. Bielenberg and J. O'Hagan -- Housing in Ireland, 1740-2016 / E. Rowley -- Feast, famine and food poverty : food in Ireland, 1740 to the present / J. Adelman -- Literacy and education / C. O'Neill -- Health and welfare / C. Cox -- Old age, death and mourning / P. Lysaght -- Celebrations and the rituals of life / D.O Giollain -- Women and gender roles / D. Urquhart and L. Earner Byrne -- Childhood / S.-A. Buckley and S. Riordan -- Family, sex and the law / M. Luddy -- Crime and policing / M. Finnane and I. O'Donnell -- Sport, associational culture and national awareness in Ireland / W. Murphy -- Part III. Emigration, immigration and the wider Irish world -- Irish emigration in a comparative perspective / K. Kenny -- The diaspora in comparative and inter-generational perspective / B. Walter -- Minorities / E.F. Biagini -- Political violence and diasporas since 1740 / C. Nic Dhaibheid -- The Irish in Australia and New Zealand / A. McCarthy -- Mobility, money and nostalgia : the Irish in America / T. Meagher -- The Irish in Britain / R. Swift and S. Campbell -- Missionary empires and the worlds they made / S. Roddy -- Cultural transmission, the Irish associational culture and the "marching" tradition / J. MacPherson -- Immigrati
Title from publisher's bibliographic system (viewed on 25 Sep 2018).
Keywords: elektronické knihy; electronic books; Social change -- Ireland -- History; Ireland -- Social conditions; Ireland -- Economic conditions; Ireland -- Population -- History